Valuation Strategies for Series A Startups - Hafiza Marjan Khan; Dr. Sohaib Uz Zaman (Indus Journal of Social Sciences, 2025)
Tech startups are a vital part of today’s digital world. They represent innovation, transformation and a step towards a more advanced world. But securing external funding is as vital as building the right product. Series-A funding is one way of getting the required monetary help to keep a startup afloat during the initial times. The funding provides enough support to transform the minimum viable product into something scalable and fit for the use of a larger audience. Hence, the purpose of this research is to identify key factors that impacts the valuation of startups looking forward to raise series A funding. A comprehensive analysis was done on the factors like EBITDA, revenue growth, customer retention, operational efficiency, growth and profitability and management strategies. About 100 emerging Pakistani tech-startups were surveyed to make this research significant and more than half were aged between 1-3 years. The statistical results suggest that revenue and growth, high profitability and appropriate management strategy contributes in increasing the overall valuation of startups that are seeking Series-A funding whereas customer retention and operational efficiency does not guarantee a bigger cheque from the investors.